Evaluasi Potensi Wisata Bromo-Madakaripura Sebagai Ekowisata Dalam Meningkatkan Perekonomian Masyarakat Sekitar - Kurnia Maulidi Noviantoro (Fakultas Ekonomi dan Bisnis Islam, 2020)
The potential of natural tourism in Bromo and Madakaripura Waterfall which are in one regional complex are very beneficial for the people in Probolinggo. The potential possessed by Probolinggo district should be evaluated as an ecotourism area based on a SWOT analysis. The rapid development of tourism can not be separated from the fulfillment of facilities and infrastructure that supports the needs of tourists. Therefore it is necessary to examine more deeply the potential that is based on spatial perspective in order to come up with new tourism ideas and renewal of programs in tourism areas. In this case, based on the SWOT analysis and spatial location between Bromo and Madakaripura, which are very close to each other, they have different tourism potentials, so it can be suggested an alliance program between the two tourism potentials. Thus in the end it will have an impact on the economy of the community around the two attractions.